Virtual excursions as a means of improving professional foreign language skills in a non-linguistic university: cultural immersion approach - Kordon, Tamara Anatol'evna (Этническая культура, 2025)
The article discusses modern approaches to foreign language teaching, emphasizing the use of virtual excursions as an effective method that promotes the development of language and cultural skills. Virtual excursions, which utilize contemporary digital technologies such as 3D modeling and augmented reality, provide learners with a unique opportunity to immerse themselves in the language environment and broaden their cultural horizons, which is vital in the context of international communication. The aim of the study is to demonstrate the potential of using virtual excursions in foreign language teaching at a non-linguistic university. The research was conducted at the Yakovlev’s University, where future teachers participated in a series of virtual excursions focusing on the history and culture of Great Britain. The research methodology included surveys, observations, and semi-structured interviews, allowing an assessment of the students’ language preparedness and engagement before and after the implementation of the innovative teaching method. The results showed a significant improvement in language skills, perception of authentic audio and video materials, as well as knowledge of the cultural aspects of the studied language countries.